Design of Smart Medical Mask Trash Can For Public Places - Muhammad Dhafier Mu'afa; Refansyah Basu Dewa; Muhammad Raflie Pangestu; Muhammad Fiqih Al Faishal; Hari Maghfiroh (Universitas Sebelas Maret (UNS), 2021)
The Covid-19 pandemic mainly caused the sudden rise of medical mask waste. There are some steps that can be taken to reduce and manage the waste, including dissolving the mask so it cannot be use again, reduce the risk of disease transmission, and assist the workers in managing the waste of medical mask. Therefore, this paper proposes a device that can solve all the problem, which is the “Smart Medical Mask Trash Can”. This device can be used to dissolve and disinfect the mask, as well as manage the mask waste with an easy way in accordance with health protocol. The outcome show that this device can monitor the waste with an application program on a real time that can notify and organize a schedule for automatic disinfection. This tool is suitable to be placed in public places because of its high mobility and there is a lot of medical mask's waste.